The Destructive Potential of the Imagination - Gifford, Don (Hungarian Journal of English and American Studies, 2020)
Two contrary concepts dominate our understanding about human imagination—this all-but-undefinable human faculty. While one tradition contrasts the creativity of the imagination, on the one hand, and the perception of reality, on the other—often suggesting that fact (reality) and fiction (imagination) are mutually exclusive—the counter-tradition defines imagination as integral to the creation/perception of reality, what Edith Cobb calls the “preconfigurative imagination.” Drawing on these theoretical-philosophical considerations, the essay takes an interdisciplinary approach to probe the inherently adverse nature and the destructive potential of the human imagination in action. With examples from literature, cultural history, politics, and diplomacy the analysis offers the case in point and demonstrates the ways destructive imagination, impervious to rational argument, may render our ability void; as Henry James put it in “The Art of Fiction,” “to guess the unseen from the seen, to trace the implication of things, to judge the piece by the pattern.” (ÉM)